1997
DOI: 10.1002/(sici)1099-0771(199706)10:2<77::aid-bdm248>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Compensation Method and Disclosure Level on Information Search Strategy and Escalation of Commitment

Abstract: In this study we examined the extent to which compensation method and public disclosure influenced information search strategy and escalation of commitment. A laboratory experiment involving 182 student subjects employed a 3 (compensation: no‐pay, salary, and contingent) by 2 (disclosure level: public and private) fully randomized, crossed design. Results show that in light of negative feedback concerning performance results of an investment portfolio, subjects whose initial allocation decisions were announced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The prior investment (sunk cost) portrayed in hypothetical scenarios is often money, 65 typically amounts many people do not deal with on a daily basis-such as thousands or millions of dollars. 77,[83][84][85][86][87][88] Researchers have begun to consider other investment dimensions such as time 72,76,78,82,89 and effort. 69,90 Measurement Some vignettes present a choice between two options embedded within a single scenario.…”
Section: Decision Contextmentioning
confidence: 99%
“…The prior investment (sunk cost) portrayed in hypothetical scenarios is often money, 65 typically amounts many people do not deal with on a daily basis-such as thousands or millions of dollars. 77,[83][84][85][86][87][88] Researchers have begun to consider other investment dimensions such as time 72,76,78,82,89 and effort. 69,90 Measurement Some vignettes present a choice between two options embedded within a single scenario.…”
Section: Decision Contextmentioning
confidence: 99%
“…Likewise, Kernan and Lord (1989) provided evidence for attention to supportive information. In the case of failing projects, findings suggested that public justification of allocation decisions can lead to unintended consequences such as selectively searching for information that supports the initial decision (Beeler & Hunton, 1997). This conclusion was supported by experiments, which indicate that the search for retrospective information (which supports the original decision) is higher when a failed allocation decision is made public than when it remains private (Beeler & Hunton, 1997).…”
Section: Public Justification and Investments In Failing Projectsmentioning
confidence: 91%
“…In the case of failing projects, findings suggested that public justification of allocation decisions can lead to unintended consequences such as selectively searching for information that supports the initial decision (Beeler & Hunton, 1997). This conclusion was supported by experiments, which indicate that the search for retrospective information (which supports the original decision) is higher when a failed allocation decision is made public than when it remains private (Beeler & Hunton, 1997). Third, the literature on cognitive dissonance (Festinger, 1957) and forced compliance (Festinger & Carlsmith, 1959) has suggested that private opinion moves toward the position that is advocated by one's behavior or speech.…”
Section: Public Justification and Investments In Failing Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several features of it, which might not necessarily be present in organizational settings, may have amplified the escalation or may limit the generalizability of findings: a large crowd of spectators (Beeler & Hunton, 1997), identifiability of and familiarity between players (Haran & Ritov, 2014), the outgoing and active atmosphere of the classroom game, and rules for possible increments in bid sizes.…”
Section: From the Dollar Auction To The Minimal Dollar Auction Paramentioning
confidence: 99%